Web Service Management (WSM)- Architecture Patterns balancing management against complexity. - Abaas, Ramy
Web Services are rapidly emerging as important building blocks for business integration. They are finding important applications in business-to-business, business-to-consumer and enterprise application integration solutions. As such, Web Services are critical to business architecture and their reliable execution must be assured. Reliability must be a first-rank consideration for organizations deploying such solutions. The management of computer systems and applications is a discipline that is well developed and extensive. It has recently evolved to encompass Web Services.